The LEGO Mindstorms NXT 2.0 discovery book : a beginner's guide to building and programming robots - Valk, Laurens (No Starch Press, 2010)
"From the creative mind of author, robotics instructor, and frequent NXT Step Blog contributor Laurens Valk, The LEGO Mindstorms NXT 2.0 Discovery Book is packed with building and programming instructions for eight innovative robots"--Resource description page.